2022
DOI: 10.1093/gji/ggac406
|View full text |Cite
|
Sign up to set email alerts
|

Application of six-component ambient seismic noise data for high-resolution imaging of lateral heterogeneities

Abstract: Summary We develop a novel approach for imaging subsurface lateral heterogeneities using six-component (6C) ambient seismic noise data, consisting of three translational components and three rotational components. We first derive the 6C cross-correlation functions (CCFs) from ambient seismic noise data for surface waves and then apply the modified frequency Bessel (MF-J) transform to the 6C CCFs for surface wave dispersion curves. The phase velocities of Rayleigh and Love waves can be directly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Its sensitivity kernel attains large absolute values only in the vicinity of the receiver but not in the vicinity of the source (Fichtner & Igel, 2009) which means that the phase velocity is only sensitive to the local structure. Its lateral resolution can be several times smaller than one wavelength (Tang & Fang, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its sensitivity kernel attains large absolute values only in the vicinity of the receiver but not in the vicinity of the source (Fichtner & Igel, 2009) which means that the phase velocity is only sensitive to the local structure. Its lateral resolution can be several times smaller than one wavelength (Tang & Fang, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…In the past few yearsthrough the emergence of multi-component rotational ground motion instruments such as ring lasers (Igel et al, 2005(Igel et al, , 2021Schreiber et al, 2014) or fiber-optic gyros (Schreiber et al, 2009)-techniques were developed to exploit the resulting 6-degrees-of-freedom observations (6 dof, three components of rotations and three components of translations) opening a new range of opportunities in particular for single-station observations. Most notably, 6 dof observations provide direct access to local surface wave phase velocities and propagation directions through the analysis of amplitude ratios (Igel et al, 2007), which is capable of extracting the dispersion of different modes of surface waves (Tang & Fang, 2023). By applying adjoint techniques (Fichtner & Igel, 2009) to such joint observations, it could be shown that 6 dof point measurements are sensitive to near-receiver structure, eliminating the path effects of wave propagation.…”
mentioning
confidence: 99%
“…(d) Extract the phase velocity based on Equations 1-3. Among them, step (b) is to preserve the amplitude ratio information during data processing, because the phase velocity only comes from the contribution of the 6C station (Tang & Fang, 2023).…”
Section: Datamentioning
confidence: 99%
“…Equation 4provides a new approach for estimating phase velocities in anisotropic media which only depends on amplitude information. Its local sensitivity kernel allows us to monitor the local velocity with high lateral resolution that can be several times smaller than one wavelength (Fichtner & Igel, 2009;Tang & Fang, 2023; Tang…”
Section: Azimuthal Anisotropy From 6c Observationsmentioning
confidence: 99%
“…Most notably, 6 dof observations provide direct access to local surface wave phase velocities and propagation directions through the analysis of amplitude ratios [21] and waveform coherence, respectively. By applying adjoint techniques [22] to such joint observations, it could be shown that 6 dof point measurements are sensitive to near-receiver structure only with frequency-dependent sensitivity volumes [23].…”
mentioning
confidence: 99%